Wheat pasture with various supplements for fattening lambs. - Cox, R.F.; Erhart, A.B. (Kansas Agricultural Experiment Station, 2012)
Many uncertainties and notions are current concerning the use of wheat pasture for fattening lambs. In an effort to find definite information on some of these experiments on pasturing wheat have been conducted during seasons when wheat growth furnished sufficient pasture. Comparisons where made this year of fattening lambs in the lot and on wheat pasture. One lot of lambs on wheat pasture received nothing else. Addition lots were pastured on wheat and received in addition either dry roughage, bicarbonate of soda, a mineral mixture or vaccination against enterotoxaemia.
Keywords: Sheep; Wheat pasture; Weight; Gain